Using a Systemic Functional Genre-Based Approach to Promote a Situated View of Academic Writing Among EFL Pre-service Teachers - Doris Correa; Sandra Echeverri (Asociación Colombiana de Profesores de Ingles, 2017)
This article reports partial results of a qualitative study which explored the gains and challenges encountered by two groups of English as a foreign language pre-service teachers from a public university in Medellin, Colombia, in developing a situated view of academic writing through a systemic functional genre-based instructional unit. The unit was part of a written communications course and used an approach called the teaching-learning cycle. Results from the study suggest that one of the main gains was related to pre-service teachers' emerging understanding of context, purpose, and audience. One of the main challenges concerned pre-service teachers' difficulty with shifting their former views of grammar as a fixed system of rules.